Daya Saing Ekspor Lada Indonesia di Pasar Amerika dan Eropa - Putroe Balqis; Rahmat Yanuar (Forum Agribisnis, 2021)
Indonesia was one of the world's largest pepper exporters where America and some European Union countries are become the destinations of its exports. The purposes of this research was to analyze the development of Indonesian pepper exports and to analyze the competitiveness of Indonesian pepper exports in American and European market in the period 2004-2018. This research used descriptive analysis from trade data periode 2004-2018, in order to analyze the performance of Indonesian pepper. From the same data set, this study used competitiveness analysis with the Revelead Comparative Advantage (RCA) method, Export Product Dynamics (EPD), and Trade Specialization Index (ISP). The results showed that the area of crop land and production of Indonesian pepper had decreased, the development of Indonesian pepper exports was also quite volatile. Based on the calculation of RCA, Indonesia has competitiveness or comparative advantage for exports to Germany, the Netherlands, France, Italy and Belgium. The EPD value showed Indonesia was in a Retreat position in the Netherlands, Germany and Belgium. While Indonesia is in the position of Rising Star in Italy, Falling Star in France, and Lost Opportunity in America. The ISP value showed that Indonesia has strong competitiveness as an exporter of whole pepper.